JARINGAN RANTAI PASOK KOPI BIJI - Irmayani Noer; Sri Handayani (Politeknik Negeri Lampung., 2023)
Coffee agribusiness in Indonesia has grown rapidly in the last 5 years. This commodity has great potential to make a significant contribution to the post-pandemic national economic recovery (PEN) program. The results of previous studies showed that most of the coffee beans from farmers (56%) were sold in the form of dry beans (raw material), or in bulk. Meanwhile, the rapid progress of the tourism and creative economy sectors as well as the development of consumer preferences in the food and beverage business have been able to elevate premium coffee (picked red) into a potential new market for farmers. However, limited market access and supply chain systems as well as yield handling technology mean that this potential is only enjoyed by a small number of farmers. This study aims to: identify the coffee supply chain system from farmers to consumers (exporters/coffee processing industries) from West Lampung production centers to Bandar Lampung City. Based on the identification of the coffee bean supply chain system, there are eight streams of the coffee bean supply chain and several actors who are directly involved, namely farmers, collector traders, wholesalers, farmer groups, federate farmer groups, joint business groups, and consumers (exporters and industry). The results of calculations and analysis of economic added value show that most of the added value from the coffee bean supply chain channel is enjoyed by actors who are directly involved in the supply chain system. The largest value added recipients are farmers and the smallest value added recipients are collectors. Keywords: supply chain system, actors of coffe supply chain, added value of coffee bean